Compassionate Use of the ROCK Inhibitor Fasudil in Three Patients With Amyotrophic Lateral Sclerosis - Koch, Jan C.; Kuttler, Josua; Maass, Fabian; Lengenfeld, Teresa; Zielke, Eirini; Bähr, Mathias; Lingor, Paul (Frontiers in Neurology, 2020)
The Rho kinase (ROCK) inhibitor Fasudil is a promising drug for a disease-modifying therapy of amyotrophic lateral sclerosis (ALS). In preclinical models, Fasudil was shown to increase motor neuron survival, inhibit axonal degeneration, enhance axonal regeneration and modulate microglial function in vitro and in vivo. It prolonged survival and improved motor function of SOD1-G93A-mice. Recently, a phase IIa clinical trial has been commenced to investigate the safety, tolerability, and efficacy of Fasudil in ALS patients at an early stage of disease (ROCK-ALS trial, NCT03792490, Eudra-CT-Nr.: 2017-003676-31). Although Fasudil has been approved in Japan for many years for the treatment of vasospasms following subarachnoid hemorrhage and is known to have a favorable side effect profile in these patients, there is no data on its use in human patients with ALS or any other neurodegenerative conditions. Here, we report the first three cases of compassionate use of Fasudil in patients with ALS. Between May 2017 and February 2019, one male (66 years old) and two female (62 and 68 years old) subjects with probable or definite ALS according to the El Escorial criteria (one of the females having a pathogenic SOD1 mutation) were administered Fasudil 30 mg intravenously twice daily over 45 minutes on 20 consecutive working days. Blood pressure, heart rate and routine laboratory tests were constantly controlled. All three subjects tolerated the Fasudil infusions well without any obvious side effects. Interestingly, the slow vital capacity showed a significant increase in one of the patients. Taken together, we report here the first compassionate use of the ROCK inhibitor Fasudil in three ALS patients, which was well tolerated.